Preserving West Lampung Culture through the Role of the Young Generation on Social Media (Open Society Conference, 2023)
The primary objective of this research is to ascertain the extent of the younger generation's involvement in the preservation and conservation of West Lampung's cultural heritage through the utilization of social media. Employing a qualitative research approach, this study employed in-depth interviews as its research methodology. The participants in this study were selected from the cohort of active social media users belonging to the younger demographic of West Lampung. The data collected were subjected to a rigorous analysis utilizing a thematic approach to elucidate discernible patterns and emergent themes. The research findings substantiate the significant role assumed by the younger generation of West Lampung in the preservation and safeguarding of their local culture through the medium of social media. They adeptly harness these digital platforms to disseminate a broad spectrum of information encompassing West Lampung's cultural tapestry, spanning customs, traditions, artistic expressions, and the vernacular language. In doing so, they engender a heightened level of public awareness and serve as a wellspring of inspiration for their contemporaries, encouraging them to actively participate in this endeavor of cultural preservation. This research serves to deepen our comprehension of the latent potential harbored by social media as a potent instrument for the preservation of local culture. Through the proactive engagement of the younger generation in harnessing the capabilities of social media, the rich cultural heritage of West Lampung stands poised for perpetuation and dissemination to forthcoming generations.